How we compare: Society for Academic Emergency Medicine faculty membership demographics. Issue 1 (23rd June 2022) - Bennett, Christopher L.; Ling, Albee Y.; Agrawal, Pooja; Pierce, Ava; Pasao, Melissa A.; Ray, Douglas; Cleveland Manchanda, Emily C.
Abstract: Background: The Society for Academic Emergency Medicine (SAEM) has a core value to promote a diverse workforce for patients, providers, and learners. Understanding the organization's membership demographics and how that compares to the academic emergency medicine (EM) workforce is prerequisite to the success of this core value. Methods: We obtained 2020 faculty membership data sets from the Association of American Medical Colleges (AAMC) and SAEM; data included self‐reported sex, race and ethnicity, and academic rank (professor, associate professor, assistant professor, and instructor). We employed standardized mean difference (SMD) to quantify difference in proportions between data sets. Results: We identified 5874 (AAMC) and 2785 (SAEM) faculty. The AAMC (38.3%) and the SAEM (41.3%) had similar proportions of overall female faculty (SMD 0.063) although SAEM (compared to AAMC) had a higher proportion of female full (25.5% vs. 20.5%, SMD 0.121) and assistant (46.5% vs. 41.2%, SMD 0.106) professors. With the exception of Hispanic instructors, SAEM (compared to AAMC) also had higher proportions of Black and Hispanic female faculty at all ranks (SMD ranging from 0.109 to 0.777). Conclusion: SAEM faculty demographics generally reflect that of the academic EM workforce demographics reported in the AAMC database and that overall, the proportions of female, Black, and Hispanic faculty in SAEM are slightly larger than those in the AAMC database. However, faculty who identify as Black or Hispanic in both the AAMC and the SAEM databases (compared to the overall U.S. population) are dramatically underrepresented.